2016
DOI: 10.14814/phy2.12860
|View full text |Cite
|
Sign up to set email alerts
|

The role of GαO‐mediated signaling in the rostral ventrolateral medulla oblongata in cardiovascular reflexes and control of cardiac ventricular excitability

Abstract: The heart is controlled by the sympathetic and parasympathetic limbs of the autonomic nervous system with inhibitory signaling mechanisms recruited in both limbs. The aim of this study was to determine the role of inhibitory heterotrimeric G proteins in the central nervous mechanisms underlying autonomic control of the heart and its potential role in arrhythmogenesis. Mice with conditional deletion of the inhibitory heterotrimeric G protein Gα O in the presympathetic area of the rostral ventral lateral medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although both the loss of sinus rhythm during the clonic phase and the abrupt return of sinus rhythm during mechanical resuscitation closely coincide with respiratory changes, the pO2 and pCO2 are undoubtedly very different at these two points in time. Furthermore, several studies in mice have demonstrated that the initial response to hypoxia, ≤12% O 2 , is a reflex increase in heart rate followed by a decrease with no loss of P-wave over several minutes [1619]. Hypercapnia (5%-6% CO 2 ) decreases heart rate, but does not eliminate SA nodal activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both the loss of sinus rhythm during the clonic phase and the abrupt return of sinus rhythm during mechanical resuscitation closely coincide with respiratory changes, the pO2 and pCO2 are undoubtedly very different at these two points in time. Furthermore, several studies in mice have demonstrated that the initial response to hypoxia, ≤12% O 2 , is a reflex increase in heart rate followed by a decrease with no loss of P-wave over several minutes [1619]. Hypercapnia (5%-6% CO 2 ) decreases heart rate, but does not eliminate SA nodal activity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies in mice have demonstrated that the initial response to hypoxia, ≤12% O 2 , is a reflex increase in heart rate followed by a decrease with no loss of P-wave over several minutes [1619]. Hypercapnia (5%-6% CO 2 ) decreases heart rate, but does not eliminate SA nodal activity [19,20]. Thus, it seems unlikely that alterations in blood gases per se contribute to the rapid changes in heart rhythm during C/T seizure.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6J mice, bred on site or purchased from The Jackson Laboratory, were used as wild-type controls for these studies. Mice lacking either Gα o or Gα i2 selectively in atrial/SAN tissue were generated by crossing the SLNCre driver mouse line (34) with floxed versions of either Gα o (35) or Gα i2 (32), resulting in SLNCre:Gα o fl/fl and SLNCre:Gα i2 fl/fl mouse lines, respectively. Male and female mice were group-housed on a 12-h light/dark cycle, given free access to food and water, and used for experiments at ages 8 to 12 wk.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that aspartate aminotransferase (AAT), a key enzyme in endogenous SO 2 generation, is produced in the mammalian brain [5] and causes hypertension and tachycardia [6]. The central nervous system (CNS) is known to be involved in regulating arterial pressure [79]. The present study was designed to test the hypothesis that SO 2 regulates blood pressure (BP) by a central mechanism.…”
Section: Introductionmentioning
confidence: 99%